Investigating of AI tools' Enhancement on the English Writing Skills among Non-Native Speakers - Mohammed Hamoud Ghannam; Afaf Alwan; Baleid Taha Shamsan; Ayat Abdullah; Enas Ameen; Aya Hassan; Mlak Faez; Ayman Hatem; Bushra Abdullah Rashed (مجلة الدراسات الاجتماعية)
This document addresses, using examples of popular AI tools including Grammarly and Hemingway, how such similar tools assist their use in improving non-native English learners' writing through real-time feedback on grammatical, syntactical, vocabulary-related, coherence, and clarity issues. Interviews were conducted with students and language instructors and together with analysis of the results underscore several issues-both challenges and advantages being that of implementing AI in writing education.